Perhitungan Harga Pokok Penjualan Kaos Sablon Menggunakan Metode Full Costing Pada IKM Sinovec - Nugraha, Luthfi Aditya; Debora, Fransisca (Fakultas Teknik Universitas Tulang Bawang, 2024)
Sinovec SME is a medium-sized enterprise specializing in the production and services of garment convection, with its flagship product being screen-printed shirts. This study focuses on the calculation of the cost of goods sold using the full costing method, which takes into account all production costs, including raw materials, direct labor, and both variable and fixed factory overhead costs. The research combines field studies to gather necessary data and literature reviews to compare with previous research and provide references. Based on the profit and loss statement, it's evident that Sinovec achieved a profit of Rp 1,351,500 from selling 300 shirts in one month. With the cost of goods sold per shirt and an 18% profit margin from a selling price of Rp 70,000, Sinovec managed to attain significant profits. This demonstrates efficiency in cost management and appropriate pricing strategies. Consequently, Sinovec is able to maintain a healthy profit margin in its business. Accurate calculations and suitable pricing strategies are key to Sinovec's success in optimizing profitability in the competitive garment convection market. Keywords: Cost Production, Full Costing, Screen Printing